Sammlung Rywelski : Auktion 775. (Köln : Kunsthaus Lempertz Köln, 1999)
Alvermann, Hans Peter ; Baruchello, Gianfranco ; Berke, Hubert ; Beuys, Joseph ; Böhmler, Claus ; Böttger, Klaus ; Brecht, George ; Brüning, Peter ; Burghardt, Ursula ; Buthe, Michael ; Carmi, Eugenio ; César ; Christo ; Dine, Jim ; Eggenschwieler, Franz ; Fernandez, Arman ; Filliou, Robert ; Gaul, Winfred ; Grützke, Johannes ; Hadengue, Sébastien ; Höke, Bernhard ; Hungerberg, Helmut ; Iannone, Dorothy ; Immendorff, Jörg ; Jones, Allen ; Knizak, Milan ; Lichtenstein, Roy ; Luther, Adolph ; Neuenhausen, Siegfried ; Nierhoff, Ansgar ; Paeffgen, C.O. ; Page, Robin ; Peintner, Max ; Picard, Lil ; Piene, Otto ; Pistoletto, Michelangelo ; Prager, Heinz-Günter ; Räderscheidt, Anton ; Ramos, Mel ; Reich, Steve ; Reinecke, Chris ; Reinert, Brigitte ; Richter, Gerard ; Roth, Dieter ; Salentin, Hans ; Schäuffelen, Konrad Balder ; Schmit, Tomas ; Schult, HA ; Schumann, Sarah ; Sommer, Ed ; Spindel, Ferdinand ; Spoerri, Daniel ; Stamm, Adolf ; Thomkins, André ; Thonett, Will ; Uecker, Günther ; Voss, Jan ; Vostell, Wolf ; Waller, Jürgen ; Weseler, Guenter ; Wewerka, Stefan ; Wiegand, Gottfried
biografie
boek